2011
DOI: 10.1111/j.1365-2966.2011.20187.x
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy-scale outflows driven by active galactic nuclei

Abstract: We present hydrodynamical simulations of major mergers of galaxies and study the effects of winds produced by active galactic nuclei (AGN) on interstellar gas in the AGN’s host galaxy. We consider winds with initial velocities ∼10 000 km s−1 and an initial momentum (energy) flux of ∼τw L/c (∼ 0.01  τw L), with . The AGN wind sweeps up and shock heats the surrounding interstellar gas, leading to a galaxy‐scale outflow with velocities ∼1000 km s−1, peak mass outflow rates comparable to the star formation rate an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
255
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(283 citation statements)
references
References 41 publications
28
255
0
Order By: Relevance
“…Fig. 2 shows the mass of the black hole at the time the BHAR reaches its maximum value as function of the stellar velocity dispersion of the resulting elliptical galaxy, on how to calculate the latter we refer to Debuhr et al (2011). The results are consistent with the observed correlation from Gültekin et al (2009) indicated by the solid line.…”
Section: T H E G E N E R a L P I C T U R Esupporting
confidence: 74%
See 2 more Smart Citations
“…Fig. 2 shows the mass of the black hole at the time the BHAR reaches its maximum value as function of the stellar velocity dispersion of the resulting elliptical galaxy, on how to calculate the latter we refer to Debuhr et al (2011). The results are consistent with the observed correlation from Gültekin et al (2009) indicated by the solid line.…”
Section: T H E G E N E R a L P I C T U R Esupporting
confidence: 74%
“…Here we use v w = 10 4 km s −1 following Debuhr et al (2012). As thus not all of the mass that is made available by the accretion disc enters the black hole, its accretion rate must be reduced accordinglẏ…”
Section: Agn Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of active galaxy nucleus (AGN) and the associated feedback is intensively discussed, as well as the pairing of black holes in mergers (see e.g. Lagos et al, 2008;Narayanan et al, 2008;Blecha et al, 2011;Debuhr et al, 2011;Sijacki et al, 2011, among many others).…”
Section: Forty Years Of Numerical Simulationsmentioning
confidence: 99%
“…However, starformation can also be quenched or suppressed through powerful galaxy-scale outflows driven by energy released during AGN accretion (e.g. Di Springel et al 2005;Bower et al 2006;Croton et al 2006;Schawinski et al 2007;Nesvadba et al 2010;DeBuhr et al 2012;Maiolino et al 2012;Karouzos et al 2014). A large number of AGN host galaxies lie in the 'Green Valley' of the galaxy colour-magnitude diagram (e.g.…”
Section: Introductionmentioning
confidence: 99%